The Fundamentals of Islamic Education - Reni Cahyati; Meilan Kiftya; Chairani (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2025)
The fundamentals of Islamic education are the reference point for the source of truth and strength that can lead to the desired activities. The Quran, as the first and primary source in Islamic teachings, teaches and invites humans to always use their intellect and thinking. Islamic education is based on the elements of values contained in the teachings of Islam. One of its goals is to educate the public about the true faith to become true Muslims The purpose of this research is to assess the effectiveness of Islamic education in achieving established educational goals. This research aims to find out how and how to conduct an evaluation, so that in the teaching and learning process of a school can be seen the developments that occur, so that an educator can choose what learning methods and methods are suitable for teaching students so that the students can understand and also understand the learning provided by the teacher, so this evaluation is very important to be carried out in schoolsThe method used in this research is a literature review, gathering information from journals, the internet, and other relevant sources. The research findings show that the fundamentals of Islamic education have very important components in education and in achieving good educational goals.